An Important Cause of Morbidity in Preterm Babies; Necrotizing enterocolitis: A Two-Year Evaluation - MEMİŞOĞLU, ASLI; ÖZEK, EREN; BİLGEN, HÜLYA SELVA; ÖZDEMİR, HÜLYA; KARADENİZ CERİT, KIVILCIM; CENNETOĞLU, PAKİZE (DR BEHCET UZ COCUK HASTALIKLARI VE CERRAHISI, 2019)
Objective: In our study, we aimed to evaluate the risk factors that influenced development of necrotizing enterocolitis (NEC) in preterm babies born at a gestational age below 32 weeks who were being followed up in our neonatal intensive core unit. Method: Babies who were born at a gestational age below 32 weeks in our hospital were evaluated in terms of perinatal (maternal hypertension/preeclampsia, antenatal Doppler US abnormality, intrauterine growth restriction, delayed/premature membrane rupture) and postnatal risk factors for the development of NEC. Demographic and clinical characteristics of the babies, in-hospital follow-up period, presence of respiratory distress, perinatal asphyxia, prsence of hemodynamically ptent ductus arteriosus, inotropic support, ventilator support, caffeine treatment, presence of central catheter, erythrocyte suspensio, nevidenced/clinical sepsis, and nutritional statis were recorded. IBM SPSS Statistics 21,0 program was used for statistical evaluation. Results: Eighty-five preterm babies were included in our study. The birth weighst and gestational weeks of the subjects were found to be 1190 (380-1650)gs and 29 (21-31) weeks, respectively. The birth weight and gestational week were found to be significantly lower in the subjects who developed necrotizing enterocolitis compared to the subjects who did not (p:0.005; p:0.035). The incidence of NEC was found to be 11.7% (n:10) in preterm babies. Doppler ultrasonography revealed abnormal findings in five of the subjects who developed NEC and in 12 of the subjects who did not develop NEC; this difference was statistically significant (p:0.002). Surgical laparotom, and surgical resection were performed in five infants. Penrose drain was inserted in one infant at bedside. The mean birth weight and gestational week of these cases were found to be significantly lower compared to the ones who did not require surgery (p:0.015; p:0.042). In 3.5% of the babies tranfusion-rlated NEC was detected. The mortaisty rote in infants who developed NEC was 40 percent. Conclusion: Especially premature babies with lower gestational week and and very low birth weight, whom cannot tolerate minimal enteral feeding, and have abnormal Doppler ultrasound findings or blood transfusion history should be monitored more carefully.
Keywords: Necrotizing enterocolitis; preterm; risk factors; incidence; BIRTH-WEIGHT INFANTS; RISK-FACTOR; CAFFEINE THERAPY; ASSOCIATION; OUTCOMES; APNEA